En la conversación fluía. Arte verbal, consideraciones emic y procesos conmemorativos judíos argentinos - Fischman, Fernando (2008)
This article examines the connections between the present and the pastestablished by Argentine Jews through the performance of verbal art expressionsand metapragmatic considerations about them. The work focuses specifically onhow certain expressions of the poetics of speech shape group memory. In particular,it deals with one narrative genre according to the utterers' definition and theiruse of it. Thus, the article shows the ways by means of which through the performanceof speech play in informal contexts, the narrators, Argentine born children ofJewish immigrants, establish axes of continuity and discontinuity with different pasts:one experienced by the speakers themselves or their ancestors, another onepertaining to Jewish life in Eastern Europe, and one originated in sacred texts.